For Sustainable Career Development: Framework and Assessment of the Employability of Business English Graduates - Tong, Minjun; Gao, Tianyue (Frontiers in Psychology, 2022)
Employability is an important indicator of the competency of the employees. Employability model is a useful analytical framework for studying the ever-changing relationship between higher education and the job market. At present, the demand for business English graduates is increasing, however, there is a skill gap between their educational readiness and the recruitment requirements. In order to solve this problem, this study adopted mixed methods research and carried out the research design according to the exploratory sequence design to construct an employability model for business English graduates. A 46-item scale was developed to measure the employability of business English graduates’ employability. After assessment, it was found that the employability of business English graduates was multi-dimensional, with 3 dimensions—professional knowledge, generic competencies and career management and 10 sub-dimensions—English language skills, foreign trade competencies, computer & internet application skills, social skills, learning & development, personal traits, thinking ability, work ethics, career identity & planning, and service awareness. This study verified that the employability of business English graduates reached the standard of talent training and met the requirements of employers. There were employability differences in gender, places of origin and educational institutions. From this study, it could be inferred that cultivation of business English majors should be multi-dimensional.